"On Water" Sustainable Synthesis of 1, 5‐Disubstituted Tetrazoles via Ugi‐Azide Reaction through Perturbation of Kosmotropes Using Nacl. Issue 30 (23rd October 2017) - Dandia, Anshu; Khan, Shahnawaz; Sharma, Ruchi; Parihar, Sonam; Parewa, Vijay
Abstract: "ON WATER" acceleration of Ugi‐Azide reaction has been devised as a novel synthetic route for the one‐pot synthesis of 1, 5‐disubstituted tetrazoles using NaCl. Due to the formation of kosmotropes, reaction does not occur in aqueous media alone which explains the low extent of hydrophobic interaction of reactants with water. However, presence of NaCl agitates the water kosmotropes and enhances the hydrophobic interactions of reactants with aqueous phase and desired product was isolated in excellent yield. Thus, NaCl plays a decisive, indispensable and unprecedented role through the perturbation of kosmotropes of water on Ugi‐azide reaction in aqueous media. Among the various as synthesized tetrazoles, ferrocenyl 1, 5‐disubstituted tetrazoles showed excellent β–hematin inhibitory activities (IC50 <3.5 μg/ml) as compared to reference drug chloroquine. Further we have also showed the synthetic utility of these compounds by Pd mediated post reaction transformation through an example. Abstract : "ON WATER" acceleration of Ugi‐Azide reaction has been devised as a novel synthetic route for the one‐pot synthesis of 1, 5‐disubstituted tetrazoles using NaCl. The NaCl agitates the water kosmotropes and enhances the hydrophobic interactions of reactants with aqueous phase and desired product was isolated in excellent yield.